The role of seismic hazard modeling on the simplified structural assessment of an existing concrete gravity dam. (December 2021) - Kita, Alban; Lupattelli, Arianna; Venanzi, Ilaria; Salciarini, Diana; Ubertini, Filippo
Highlights: The seismic performance of a concrete gravity dam is investigated under different hazard models. Combined effects of horizontal and vertical accelerations are considered for structural assessment. Site-specific PSHA models provide more severe loading conditions than probabilistic code-based ones. The vertical seismic component is particularly detrimental if inertial force acts upwards. Abstract: Worldwide spread, dams are exposed to various types of hazards, among which, the seismic one poses a real challenge about their structural safety. Given a quite significant number of concrete gravity dams in Italy, they are of particular concern in this paper. While the behavior of their critical structural components is generally well understood and modeled, the results of their seismic assessment are highly affected by the adopted seismic hazard model. In order to shed some light on this aspect, this paper presents numerical investigations considering a representative concrete gravity dam located in a high Italian seismic area as case study. A site-specific seismotectonic study is adopted and differences with respect to probabilistic code-based provisions are discussed. Afterwards, simplified analyses are carried out to investigate the influence of the vertical seismic component, often neglected in practical applications. Results demonstrate that the predicted dam seismic performance highly depends upon the chosen seismic hazard model, with the seismogenetic seismic hazard model being more demanding than code provisions. Furthermore, vertical acceleration deserves special attention because it is, on the one hand, the most uncertain seismic component, while on the other hand, it is sometimes the limiting factor in the assessment.